Peningkatan Pemahaman Harga Pokok Produksi pada Pengrajin Bambu di Bawuran, Bantul - Bintang Kasih Abadi; Lilik Ambarwati (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service program focuses on improving the understanding of the calculation of Cost of Goods Manufactured (COGS) for bamboo craft business actors in Bawuran Village, Bantul. The main problem faced by bamboo craftsmen is the limited understanding in calculating COGS, which has an impact on the inaccuracy of selling prices and difficulties in accessing formal financing. Through intensive counseling and mentoring methods, this program aims to increase the capacity of artisans in identifying cost components and systematically calculating COGS. The program implementation involved a series of structured stages, starting from coordination with village officials, preparation of training materials, to direct practice of COGS calculation with pre-test and post-test measurements conducted by 30 craftsmen. The pre and post test results showed that there was an increase/change in bamboo craftsmen's knowledge of COGS calculation from the pre-test to the post-test results. Reflected when the pre-test was carried out, the average value of 30 craftsmen increased from 52.65% to 70.84% from both aspects of the knowledge given to the calculation of COGS. The technical aspect shows the ability of craftsmen to calculate production costs more accurately. The craftsmen are now able to set a more competitive selling price based on the correct COGS calculation. This program not only contributes to improving the professionalism of bamboo craft business management, but also provides an empowerment model that can be replicated in other areas with similar business characteristics.